Det ludiske begær: Begær og frelse hos Hrotsvit af Gandersheim - Skinnebach, Laura Katrine (Periskop – Forum for kunsthistorisk debat, 2023)
Hrotsvit of Gandersheim (ca. 935-975), wrote and dramatized legends and plays revolving around the topic of carnal desire (negative) and how to fight it with faith (positive). This article argues that the performance of her plays created ludic play spaces in which the nuns and other potential participants could internalize both the experience of lust and the sweet pain of rejecting it.